A fast frequency estimation algorithm and its application in transformer terminal unit. Issue 1 (1st February 2022) - Li, Cheng; Li, Jun; Chen, Zhiming
Abstract: To accurately obtain the frequency of voltage and current signals and form the basis for the analysis of power quality in the Transformer Terminal Unit (TTU), a Hanning window and interpolation algorithm is proposed to estimate the signal frequency. The principle of the algorithm is introduced, and the computer program is written. At the same time, the voltage signals with different frequencies are numerically generated and the real voltage is measured, and the signal frequency is estimated by using the algorithm. The results reveal that the proposed method can accurately estimate the signal frequency for TTU, and the maximum error of frequency estimation is only 2 mHz when the signal frequency varies in the range of 49.8-50.2 Hz. However, the maximum error estimated by the FFT algorithm is up to 0.2 Hz. The computation time of the Hanning window and interpolation algorithm is only 1.29 times that of the Fast Fourier Transform algorithm. The work lays the foundation for accurate and rapid estimation of voltage and current signal frequency in TTU.